Foreign Aid, External Debt and Economic Growth in Africa: It all Depends on Governance - ENOCK MWAKALILA (African Journal of Governance and Development, 2019)
This study empirically analyses the impact of foreign aid and external debt on economic growth in Africa, considering governance indicators. Panel data was collected for 39 countries in Africa spanning across 20 years from 1996 to 2016. Ordinary Least Square (OLS), Fixed Effects, and System Generalised Method of Moment (GMM) estimation techniques was used for the analysis. The results are robust in a sub-sampling analysis based on income level, years, aid and debt categories. The results first suggest that in general, both foreign aid and external debt have a negative impact on the African economy but some African countries that have strong governance indicators are the ones that benefit from foreign aid and loans in improving their economy. Second, foreign aid from the U.S. has a detrimental, negative impact on the African economy compared to that from EU countries. Finally, foreign aid brings more harm to lower income countries compared to upper and lower-middle-income countries.